MENINGKATKAN AKTIVITAS HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn PADA MATERI HAK ASASI MANUSIA (HAM) DENGAN MENGGUNAKAN MODEL JIGSAW DI KELAS X4 SMA NEGARI 10 BANJARMASIN - Dini Maylinda Kusumawati (Jurnal Pendidikan Kewarganegaraan, 2014)
Dini Maylinda Kusumawati, 2013. Improving Student Learning Outcomes Activities In PKN Learning Materials for Human Rights (HAM) Using Model Jigsaw Classroom Exp X4 Negari 10 Banjarmasin. Supervisor (I) H. Sarbaini (II) Mariatul Kiptiah .The learning process in the classroom X4 Civics SMAN 10 Banjarmasin tend not achieve the expected results . Conditions of low activity affects the quality of student learning in the classroom . Learning that takes place in a class of students who are good looks alone were active when expressed opinion, this situation results in students who are still not familiar with the material described teachers feel embarrassed to ask and express their opinions because they feel unappreciated . Lack of democratic attitudes of students can be seen from the low motivation of democracy students in the group discussions . Students pay less attention to the teacher explaining and self-absorbed , only a few students were able to catch the teacher explained the material . This resulted in poor learning outcomes .The purpose of the study was : (1) To determine the activity of teachers in applying the Jigsaw learning model class X4 human rights materials SMAN 10 Banjarmasin (2) To raise the students in learning activities through the application of human rights materials Civics learning model SMAN 10 Jigsaw X4 class Banjarmasin (3) To improve learning outcomes of students in the subject matter of human rights in Civics class X4 SMAN 10 Banjarmasin .Data collection techniques used in action research (PTK) is the observation , documentation and test results of study conducted through several cycles , the first cycle and second cycle .The results of this study indicate (1) Teaching teachers to implement learning models Jigsaw takes place smoothly. In the first cycle of learning in teacher qualifications good enough and the second cycle has increased very well with good qualifications.(2) Activities of students has increased very well with good qualifications.(3) The learning process is applying the Jigsaw model can increase the activity of students and student learning outcomes .Based on these results, it is suggested that the school can determine langah and school policies towards better learning improvement. Civics teacher, should mengtadakan renewal in the learning process, especially the Jigsaw model, so as to achieve optimal learning implementation.Keywords: Activity, learning outcomes Civics, Jigsaw